Tourch Infections in Mothers with Bod as a Cause of Neonatal Miscarriages and Fetal Malformation in Duhok Province, Kurdistan Region/ Iraq - Al-Saeed, Adel T.; Abdulmalek, Iman Y.; Ismail, Haifa G. (Science Journal of University of Zakho, 2015)
This study was performed to demonstrate the effect of TORCH agents on pregnancy outcome of 84 mothers with BOD, the number of single, twice, triple, four and more miscarriages were 102 (55.4%), 50 (27.2%), 27 (14.7%) and 5 (2.7%), respectively. Out of 102 BOH pregnant women with single miscarriage, 43 (42.2%) and 2 (4.9%) were seropositive for anti T. gondii IgG and IgM, respectively, 89 (87.3%) and 17 (16.7) were seropositive for anti CMV IgG and IgM, respectively,  63 (61.8%) and 3 (2.9%) were seropositive for anti Rubella IgG and IgM, respectively and 63(61.8%) and 14(13.7) were seropositive for HSV-2 IgG and IgM, respectively. Regarding women with twice miscarriage, 1 (2.0%), 14 (28.0%) were seropositive for T. gondii anti IgG and IgM, respectively, 16 (8.0%), 43 (86.0%) were seropositive for CMV anti IgG and IgM, 29(58.0%), respectively. The IgG of anti Rubella was recorded in 29 (58.0%) no any case for anti IgM. and 29 (58%) and 3 (6.0%) were positive for HSV-2 anti IgG and IgM, respectively. The number of cases with triple miscarriages, 8 (11.1%) were seropositive for anti T. gondii IgG antibodies, while no any case was found against IgM antibodies. Only, 3 (4.2%), 22 (30.6%) were seropositive for anti CMV IgG and IgM respectively. The seropositivity of anti Rubella, anti HSV-2 IgG and IgM antibodies in group with triple miscarriages were recorded in 12 (16.7%), 10 (13.9%), 0 (0.0%) and 3 (4.2%) respectively. The number of cases with four and more miscarriages, all (100%) were seropositive for CMV anti IgG and IgM, and  one (20%) for T. gondii  anti IgG and IgM, while 2 (40%) and 4 (80%),were seropositive for anti Rubella and anti HSV-2 IgG, respectively. Also the results indicated that 134 (72.8%) of all examined pregnant women with BOH have  history of miscarriages,14 (7.6%) congenital malformation, 13 (7.1%) intrauterine growth retardation,10 (5.4%) premature labor and 13 (7.1%) still birth. with the predominant of anti CMV IgG and IgM antibodies.
Keywords: Women with BOD; TOURCH; Pregnancy outcome